ANKLE PUMPING EXERCISE MENINGKATKAN NILAI ANKLE BRACHIAL INDEX (ABI) - Abdilah Septiana Putri Dila; Nova Nurwinda Sari; Sri Maryuni (Jurnal Kesehatan Panca Bhakti Lampung, 2026)
Diabetes mellitus is a metabolic disease whose incidence continues to increase both in Indonesia and in the world. Patients with diabetes mellitus will experience hyperglycemia which can cause various complications, one of which is impaired peripheral blood circulation in the legs. The purpose of this study was todetermine the effect of Ankle Pumping Exercise on the value of the Ankle Brachial Index (ABI) in patients with Type 2 diabetes mellitus at the Banjarsari Health Center, Metro Utara District in 2022. This type of research is quantitative, Quasi Experiment design with a one group pretest and posttest design approach. The population in this study were all people with diabetes mellitus with circulation disorders recorded in March 2022 at the Banjarsari Health Center, Metro Utara District as many as 72 respondents.The number of samples as many as 30 respondents with a sampling technique using purposive sampling. The analysis test used the dependent t test. The results showed that the average value of the Ankle Brachial Index (ABI) before being given Ankle Pumping Exercise was 0,93; The average value of the Ankle Brachial Index (ABI) after being given Ankle Pumping Exercise is 0,98. The results of the T-test statistic test obtained a p-value of 0,001 (p-value < 0,05), it can be concluded that there is an effect of Ankle Pumping Exercise on the Ankle Brachial Index (ABI) Value in Patients with Type 2 Diabetes Mellitus at the Banjarsari Health Center, Metro Utara District in 2022 It is hoped that the results of this study can be used as an alternative for respondents to increase circulation in the feet as an effort to prevent diabetic foot ulcers.